Valores de ferritina sérica em beta talassemia heterozigota - Estevão, Isabeth F.; Souza, Maria Cristina S.; Manzato, Antonio J. [UNESP]; Bonini-Domingos, Claudia R. [UNESP] (Associação Brasileira de Hematologia e Hemoterapia e daSociedade Brasileira de Transplante de Medula Óssea, 2010)
A low iron level, the commonest nutritional deficiency in the world, is a public health problem in developing countries. on the other hand, an excessive amount of iron is toxic, causing several organic dysfunctions, such as diabetes, cirrhosis, endocrinopathies and heart disease. Researchers have reported an association of iron overload with beta-thalassemia. The aim of this paper was to compare the serum ferritin levels of women with the beta-thalassemia trait. The results of serologic tests of 137 women of childbearing age were analyzed; 63 had the beta-thalassemia trait and 74 had Hb AA. In the beta-thalassemia carriers, the median ferritin value was 51.90 ng/mL and in the non-carriers 31.60 ng/mL (p = 0.0052). Levels of less than 20 and above 150 ng/mL were observed in 28% and 3% of the non-carriers and in 16% and 11% of the carriers, respectively. With these results it is possible to conclude that women in the reproductive age with the beta-thalassemia trait present higher ferritin levels in the northeastern region of São Paulo State. Further studies are necessary to clarify possible genetic and/or environment factors which interfere in iron absorption.
Serum ferritin levels in beta thalassemia carrier
Keywords: Beta-thalassemia; ferritins; iron deficiency